A Wide-Band High-Resolution Transmitter for Optical Isolation Amplifier. (19th March 2020) - Chen, Chengying; Bai, Lixia; Zhu, Yunrong; Wu, Tiancheng
Abstract : A wide-band and high-resolution transmitter of optical isolation amplifier is proposed for switching power supply isolation and servo motor drive applications. The transmitter is based on the chopper-stabilized technique and sigma delta modulator. A built-in common-mode voltage circuit of switched capacitor is proposed to ensure the stability of input DC common mode. Meanwhile, the feedback capacitor is used to improve the driving ability, which helps to avoid a buffer with large input swing. The circuit is tapeout with GF CMOS 0.18 μ m 1P6M process with 5 V power supply. The test results show that in 5 V supply voltage, the input swing of transmitter is 2 V and the effective signal bandwidth is 110 kHz. And the output resolution achieves 11 bit.